Pengaruh Pupuk Organik Padat dan Varietas pada Produktivitas Tebu (Saccharum officinarum L.) - Eka Risdianti Asmaning Ayu; Wiwik Indrawati; Albertus Sudirman (Politeknik Negeri Lampung, 2017)
Sugarcane is one of the main sugar-producing commodities in Indonesia. The one of the efforts to increase the production and yield of sugarcane can be done by fertilization using organic fertilizer and the use of improved varieties. The aim of this research are to get optimal rate of solid organic fertilizer, the best sugarcane variety, and interaction between solid organic fertilizer rate and variety on productivity of sugarcane. The study was conducted in December 2015 until December 2016 at Teaching Farm and Chemical Analysis Laboratory, State P olytechnic of Lampung. The research used Factorial Random Block Design method, with two factors. The first factor is the rate of solid organic fertilizer (Control, 1.000 kg.ha-1, 1.500 kg.ha-1, and 2.000 kg.ha-1), whereas the second factor is sugarcane varieties (GMP 3, GMP 19, and SS 57). The data of the research were analyzed by analysis of variance and Â if the result was significantly different then continued by using LSD test of 5% level. The results showed that there was interaction between the use of solid organic fertilizer 1000 kg.ha-1 and GMP 3 varieties on variable length of sugarcane stem. The productivity of sugarcane crops can be improved by the application of 1000 kg.ha-1 solid organic fertilizer which influences the variables of sugarcane quantity per lube and the number of sugarcane segments. The best variety that can be used to increase the productivity of sugarcane is GMP 3.Keywords: solid organic fertilizer, sugarcane productivity, sugarcane varieties